Role of Circadian Rhythms in Major Plant Metabolic and Signaling Pathways - Venkat, Ajila; Muneer, Sowbiya (Frontiers in Plant Science, 2022)
Plants require an endogenous regulatory network and mechanism to cope with diurnal environmental changes and compensate for their sessile nature. Plants use the circadian clock to anticipate diurnal changes. Circadian rhythm predicts a 24-hour cycle with 16 hours of light and 8 hours of darkness in response to abiotic and biotic factors as well as the appropriate temperature. For a plant's fitness, proper growth, and development, these rhythms synchronize the diurnal photoperiodic changes. Internal pathway, central oscillator, and output pathway are the three components that make up the endogenous clock. There are also transcriptional and translational feedback loops in the clock, which are dependent on the results of gene expression. Several physiological processes, such as stress acclimatization, hormone signalling, morphogenesis, carbon metabolism, and defense response, are currently being investigated for their interactions with the circadian clock using phenotypic, genomic, and metabolic studies. This review examines the role of circadian rhythms in the regulation of plant metabolic pathways such as photosynthesis and carbon metabolism, as well as developmental and degenerative processes such as flowering and senescence. Furthermore, we summarized signalling pathways related to circadian rhythms, such as defense response and gene regulatory pathways.